Fabrication of 3D metallic glass architectures by a mold-strain-set method. (June 2022) - Wu, Yupeng; Kang, Yongping; Xie, Yiling; Xiang, Xiaojian; Shui, Langquan; Schroers, Jan; Liu, Ze
Graphical abstract: Highlights: A strain-formed-released method is introduced to fabricate 3D metallic-glass architectures with designed complex structures. The aspect-ratio of 3D metallic-glass architectures fabricated by the strain-formed-released method can be up to three. The fabricated 3D metallic-glass architectures show excellent dynamic/static mechanical performance. The 3D metallic-glass architectures of different designs can match specific functions in a wide range of fields. Abstract: Metallic glasses (MGs) are considered as promising materials for microelectromechanical systems (MEMS) due to their excellent mechanical properties combined with unique net shape formability. However, the prevalent fabrication of MG MEMS is based on semiconductor micro-manufacturing technology which is limited to 2D. This work introduces a mechanically guided manufacturing method which enables facile fabrication of free-standing 3D MG structures with predictable complex and high-aspect-ratio configuration. As examples, 3D MG architectures with out-of-plane aspect ratio up to three and MG microhelices arrays are fabricated. Most critically, we show the prepared architectures exhibit super-elasticity. Such unprecedented elasticity originates from the near-ideal elastic limit of MGs, combining with geometric optimization. Finally, we demonstrate that the microstructure of the MG 3D architectures can be tuned over a wide range, which is desirable in a wide range of applications such as sensing and energy harvesting devices.